A new species of Verbascum, V. nihatgoekyigitii (Scrophulariaceae), from southeastern Anatolia, Turkey - Çingay Burçi̇n; Karaveli̇oğullari Fai̇k Ahmet (Phytotaxa, 2016)
Verbascum nihatgoekyigitii sp. nov. (V. sect. Bothrosperma), is described as a new species to science from plants collected in southeastern Anatolia, Turkey. A detailed description, SEM micrographs and an illustration of the type specimen are included, as well as information on the ecology of the species and the IUCN red list assessment are provided. In addition, diagnostic characters of the new species are compared to the morphologically similar V. exuberans, and detailed distribution maps of those species in Turkey are also supplied.